Digital Leadership and Virtual Team Performance: A Study of Remote Work-Based Organizations - Djunaedi Djunaedi (PT. Anagata Sembagi Education, 2026)
The rapid growth of remote work and digital collaboration has transformed organizational structures and leadership practices across industries. As organizations increasingly rely on virtual teams, digital leadership has emerged as a critical capability for managing distributed employees and ensuring team effectiveness. This study aims to analyze the influence of digital leadership on virtual team performance within remote work-based organizations. This research employs a quantitative approach using primary data collected through an online survey distributed to employees working in virtual teams across remote or hybrid work environments. The sampling technique applied is purposive sampling, targeting respondents who actively participate in virtual collaboration using digital platforms. The collected data were analyzed using descriptive statistics, validity and reliability tests, and multiple regression analysis to examine the relationship between digital leadership and virtual team performance. The results indicate that digital leadership has a positive and statistically significant effect on virtual team performance. Effective digital communication, trust-building, and the strategic use of digital collaboration tools contribute to improving team productivity, coordination, and engagement in remote work environments. These findings suggest that leadership capabilities adapted to digital environments play an essential role in supporting effective teamwork in geographically dispersed teams. In conclusion, digital leadership is a crucial determinant of virtual team performance in remote work-based organizations. Strengthening digital leadership competencies can enhance collaboration, productivity, and overall team effectiveness in digital workplaces.